Strategi Kampanye Public Relations Pada Program Rebo Nyunda di Kabupaten Bandung - Ramadhan, Rafy Rizky; Solahudin, Dindin; Anugrah, Dadan (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to determine the description of the public relations campaign process in the Rebo Nyunda program in Bandung Regency. Researchers describe the campaign process starting from problem identification, campaign management, campaign evaluation. This research uses Leon Ostergaard's Ostergaard campaign model. The approach used in this research is an interpretative approach. The method used descriptive qualitative. The data collection techniques used were in-depth interviews, passive participatory observation. The results of the research show that this campaign activity applies three stages of the campaign, namely problem identification, campaign management, and evaluation.